The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5194/isprs-archives-xlii-2-w11-1089-2019
|View full text |Cite
|
Sign up to set email alerts
|

Bim for Museums: An Integrated Approach From the Building to the Collections

Abstract: The paper discusses the first outcomes of an ongoing research activity aimed at developing a general BIM-based methodology for the organization and the management of the information needed for maintenance and safety assessment of museums. The Galleria dell'Accademia di Firenze (Florence, Italy) which has a very complex spatial organisation as a result of transformations occurred over the centuries, has been considered as an illustrative application of the proposed methodology. One of the specific elements whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…The 3D reconstruction was executed using Agisoft Metashape (Agisoft, St. Petersburg) photogrammetry software. The elaboration process is composed of different phases (Tucci et al 2019;Pierdicca et al 2020):…”
Section: Case Studiesmentioning
confidence: 99%
“…The 3D reconstruction was executed using Agisoft Metashape (Agisoft, St. Petersburg) photogrammetry software. The elaboration process is composed of different phases (Tucci et al 2019;Pierdicca et al 2020):…”
Section: Case Studiesmentioning
confidence: 99%
“…Previous research has already shown how the management of museums can benefit from visually structured databases (Tucci et al, 2019a;Tucci et al, 2019b). BIM models (or H-BIM, in the case of museums in historic buildings) including data and 3D representation of works of art help museum managers in decision making by correlating information about the collections and the spaces in which they are located.…”
Section: Virtual Reality For Curatorsmentioning
confidence: 99%
“…In order to correlate the GPR survey with the overall geometry of the building, a laser scanner survey has been performed (Tucci, Bonora, Conti, & Fiorini, 2017). A terrestrial laser scanner samples opaque surfaces with high accuracy and resolution (Tucci et al, 2019). The device emits a laser beam with a pre‐set angular step and measures the distance of the surface computing the time‐of‐flight or the phase‐shift between the waveforms of the emitted and reflected signals.…”
Section: The Tls Surveymentioning
confidence: 99%